2022
DOI: 10.1186/s13059-022-02715-w
|View full text |Cite
|
Sign up to set email alerts
|

RATTLE: reference-free reconstruction and quantification of transcriptomes from Nanopore sequencing

Abstract: Nanopore sequencing enables the efficient and unbiased measurement of transcriptomes. Current methods for transcript identification and quantification rely on mapping reads to a reference genome, which precludes the study of species with a partial or missing reference or the identification of disease-specific transcripts not readily identifiable from a reference. We present RATTLE, a tool to perform reference-free reconstruction and quantification of transcripts using only Nanopore reads. Using simulated data … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…Sodium acetate has been used previously to separate DNA from RNA (Chomczynski and Sacchi 2006;Xu et al 2019), however, its efficiency when added to the aqueous phases of soil RNA extraction has not yet been reported. Mettel et al (Mettel et al 2010) used an acidic phenol (pH = 4.5) to separate DNA from RNA in soil samples, but our results, as well as those of a recently published study (de la Rubia et al 2022), show that aqueous pH is more important than the pH of the added phenol solution when separating DNA from RNA (de la Rubia et al 2022). Interestingly, we observed that the addition of low-pH sodium acetate in this step also slightly reduced the amount of humic substances (Supplementary Table 1).…”
Section: Optimization Of Rna Extraction Methods For Mineral and Organ...supporting
confidence: 63%
See 2 more Smart Citations
“…Sodium acetate has been used previously to separate DNA from RNA (Chomczynski and Sacchi 2006;Xu et al 2019), however, its efficiency when added to the aqueous phases of soil RNA extraction has not yet been reported. Mettel et al (Mettel et al 2010) used an acidic phenol (pH = 4.5) to separate DNA from RNA in soil samples, but our results, as well as those of a recently published study (de la Rubia et al 2022), show that aqueous pH is more important than the pH of the added phenol solution when separating DNA from RNA (de la Rubia et al 2022). Interestingly, we observed that the addition of low-pH sodium acetate in this step also slightly reduced the amount of humic substances (Supplementary Table 1).…”
Section: Optimization Of Rna Extraction Methods For Mineral and Organ...supporting
confidence: 63%
“…To answer this need, we designed in this study an in-house bioinformatics Abdonaser Poursalavati workflow for taxonomy analysis at different levels. Notably, using the RATTLE Pipeline (de la Rubia et al 2022), it was possible to avoid misclassifying the reads of species with the least sequencing coverage, one of the common issues when working with long-read assemblers. Thus, using this in-house workflow we analyzed the consensus sequences obtained from the clustering step in the total RNA datasets in terms of rRNA sequences and we completed the taxonomic profiling of the microbial population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, polyA-tails and the remaining SSP adapters were removed using Cutadapt [14] . De novo assembly was then performed on clean full-length reads using the RATTLE program [15] ( Table 1 ).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Nanopore DRS signals for human heart were obtained from the European Nucleotide Archive (ENA) under accession number PRJEB40410 25 . Nanopore DRS signals for HEK293 cells were obtained from the ENA under accession number ENA PRJEB40872 26 and from the NCBI Gene Expression Omnibus (GEO) under accession number TBD 15 .…”
Section: Data Availabilitymentioning
confidence: 99%